Sumbareh dalam Food Photography - Mardiana, Lidia Putri (Institut Seni Indonesia Padangpanjang, 2021)
West Sumatra has many traditional foods, one of which is Sumbareh. This food is not widely known by the public. This encourages the craftsman to visualize Sumbareh in the work of food photography. Presenting with a different concept than before, namely presenting with traditional and modern concepts. Use traditional objects and modern properties in their setup. The collection uses high-speed techniques in some works in addition to the craftsmanship also presents symbols and semiotics to convey the message. The purpose of the creation of this work is to present a new concept and arrangement from Sumbareh, to be better known by the wider community, especially young people. Sumbareh is made from real rice flour, which must be produced by itself. To eat it there are several additions in how to eat it such as Black Tapai, Cendol, White porridge, Lopis, and Brown Sugar Gravy. The creation of this work is carried out in four stages, firstly in the form of preparation by conducting research, secondly the design of the concept of the work, the three manifestations of the work, and the four presentations of the work.